Forms and methods of prevention of deviant behavior of cadets of higher educational institutions of the ministry of internal affairs of Ukraine - Kozak, Ihor (Journal of Education, Health and Sport, 2017)
The theoretical foundations of the forms of deviant behavior among students of higher educational institutions (HEIs) of the internal affairs of Ukraine are described. The existing pedagogical, psychological, social concepts are analyzed, the forms of deviation that are inherent for cadets of closed universities are identified, as well as the components of behavior that deviate from the norm. The author has identified three levels of existing contradictions in the prevention of deviant behavior: scientific and theoretical; social and pedagogical; scientific and methodical. The possible ways and methods of preventing the manifestations of deviations among cadets of higher education institutions of Ukraine’s. Indicates the need to introduce a systematic approach to the prevention of deviant behavior, including general social, special and individual prevention measures. Emphasizes the need for the development of curatorial work and psychological centers in educational institutions of the internal affairs bodies of Ukraine.